The System’s “Sticking Plaster”? Voluntary Work in late Modernity - Nowak, Marek (Studia Historiae Oeconomicae, 2012)
This paper describes the problem of voluntary work in the historical context. The analysis describes the evolution of voluntas from the classic concept of the will to contemporary practices of treating voluntary action as an element of the professional curriculum vitae. This evolution is significant for late modernity and for the crisis situation in the labour market. The voluntary now means something close to work in various labour sectors. The interpretation suggests that voluntary action nowadays is beginning to play the role of the so-called sticking plaster of the system. Finally, the author introduces the results of an empirical investigation carried out in 2011 in Poland (Poznań, Wrocław, and Gdańsk).